Development and clinical application of extendable prostheses in limb salvage surgery for primary malignant bone tumours in children: a systematic review of functional outcomes and complications - Ningkai Tang; Jiake Yang; Siyi Huang; Xiaodong Tang; Tao Ji (Bone & Joint Research)
Aims: Extendable prostheses have developed rapidly over the decades to solve limb length discrepancy (LLD) following limb salvage surgery in children and adolescents who have suffered primary malignant bone tumours. In this study, we performed a systematic review of the literature on extendable prostheses to investigate their developments and clinical outcomes, to provide evidence-based recommendations for enhancing clinical implementation and refinement. Methods: A systematic review of 46 studies with 709 invasive cases and 556 noninvasive cases was performed after searching the PubMed, EMBASE, and Web of Science databases. Results of the prosthesis survival rate, functional outcomes, and complications were extracted, recategorized, and analyzed. Results: With the increase in publication year, there was no significant change in the five-year prosthesis survival rate, while the Musculoskeletal Tumour Society (MSTS) score exhibited an upward trend. Apart from infection, the incidence of mechanical complications increased as follow-up time extended. Failed structure of invasive prosthesis was higher than in those who received a noninvasive extendable prosthesis (25.1% (123/491) vs 15.0% (70/466); p < 0.001, Power = 0.972). The mean number of additional procedures in patients who received an invasive prosthesis was higher than those who received a noninvasive extendable prosthesis (2.4 (1.3 to 3.4) vs 1.4 (0.1 to 2.7); p = 0.021), and there was no obvious clinical difference between invasive prostheses and noninvasive prostheses in infection (15.0% (88/586) vs 13.4% (68/508); p = 0.442, Power = 0.125). Infection (44/361, 12.2%) was the most common complication associated with the Stanmore JTS prosthesis, while the incidence of aseptic loosening (14/296, 4.7%) was the lowest. The mean incidence of complications in the Stanmore Mark I-IV group was higher than that in the Stanmore JTS group (68.9% (104/151) vs 36.6% (49/134); p < 0.001, Power = 0.9998). Conclusion: Despite decades of progress, extendable prostheses have shown promising results but still face challenges such as high infection rates, requiring further technological innovation for better outcomes. Cite this article: Bone Joint Res 2025;14(6):578–588.